Photo-polishing of palm oil mill effluent (POME) over UV/ZnO system - Ng, K. H.; Cheng, C. K. (2016)
The photo-polishing of POME over UV /'ZnO photocatalysis system was performed in current study. The ZnO material, with band gap energy of 3.2 eV from our UV-Vis DRS measurement, was proven responsive towards 100 W UV-irradiation of 365 nm wavelength. The effect of ZnO loading was investigated Based on the results obtained, the optimum ZnO loading for POME photomineralization was 1.0 g/L, with about 50% of COD removal recorded after 240 min of UV irradiation. It is found that all the photomineralization kinetics for all the photoreaction followed the 1st-order reaction with specific reaction rates (k) ranging froml.022 x10-3 to 3.118 x10-3 min-1 • Significantly, the organic removal efficiency was further enhanced when UV exposure was prolonged to 22 h, attaining final readings of 44 ppm of chemical oxygen demand (COD) level.